The complete typographer a foundation course for graphic designers working with type - Hill, Will 1954- (Thames & Hudson, 2010)
Provides an introductory grounding in Typography. This title teaches the essentials for the effective use of type - technical expertise and historical knowledge, an understanding of the functional and aesthetic qualities of different typefaces, and the organization of typographic space.